Nav1.5 N-terminal domain binding to α1-syntrophin increases membrane density of human Kir2.1, Kir2.2 and Nav1.5 channels. Issue 2 (19th January 2016) - Matamoros, Marcos; Pérez-Hernández, Marta; Guerrero-Serna, Guadalupe; Amorós, Irene; Barana, Adriana; Núñez, Mercedes; Ponce-Balbuena, Daniela; Sacristán, Sandra; Gómez, Ricardo; Tamargo, Juan; Caballero, Ricardo; Jalife, José; et al.
Abstract : Aims: Cardiac excitability and refractoriness are largely determined by the function and number of inward rectifier K + channels (Kir2.1–2.3), which are differentially expressed in the atria and ventricles, and Nav1.5 channels. We have focused on how Nav1.5 and Kir2.x function within a macromolecular complex by elucidating the molecular determinants that govern Nav1.5/Kir2.x reciprocal modulation. Methods and results: The results demonstrate that there is an unexpected 'internal' PDZ-like binding domain located at the N-terminus of the Nav1.5 channel that mediates its binding to α1-syntrophin. Nav1.5 N-terminal domain, by itself (the 132 aa peptide) (Nter), exerts a 'chaperone-like' effect that increases sodium ( I Na ) and inward rectifier potassium ( I K1 ) currents by enhancing the expression of Nav1.5, Kir2.1, and Kir2.2 channels as demonstrated in Chinese hamster ovary (CHO) cells and in rat cardiomyocytes. Site-directed mutagenesis analysis demonstrates that the Nter chaperone-like effect is determined by Serine 20. Nav1.5–Kir2.x reciprocal positive interactions depend on a specific C-terminal PDZ-binding domain sequence (SEI), which is present in Kir2.1 and Kir2.2 channels but not in Kir2.3. Therefore, in human atrial myocytes, the presence of Kir2.3 isoforms precludes reciprocal I K1 – I Na density modulation. Moreover, results in rat and human atrial myocytes demonstrate that binding to α1-syntrophin is necessary for the Nav1.5–Kir2.x-positive reciprocal modulation. Conclusions: The results demonstrate the critical role of the N-terminal domain of Nav1.5 channels in Nav1.5–Kir2.x-reciprocal interactions and suggest that the molecular mechanisms controlling atrial and ventricular cellular excitability may be different.